Sexuality in Islam - Bouhdiba, Abdelwahab; Sheridan, Alan. (London : Routledge, 2008)
Confronts the question of male supremacy in Islam, and the separation of the masculine and the feminine. This book provides an account of purification practices, of Islamic attitudes towards homosexuality, concubinage, legal marriage and of the sexual taboos laid down by Qur'an.
Originally published: 1975.
Keywords: Sex customs -- Islamic countries; Sex -- Religious aspects -- Islam; islam; seksuaalisuus